1985
DOI: 10.1007/bf00441772
|View full text |Cite
|
Sign up to set email alerts
|

Non-invasive oscillometric measurement of systolic, mean and diastolic blood pressure in infants with congenital heart defects after operation. A comparison with direct blood pressure measurements

Abstract: The accuracy of indirect oscillometric blood pressure measurements has been evaluated in 32 infants up to 11 months of age undergoing heart surgery. In a number of 1029 simultaneous measurements the indirect blood pressure was compared with the direct value obtained from a radial artery catheter. Cuffs of different sizes were applied. The main results were as follows: Regarding the ratio of cuff width to arm circumference, the best correlation between oscillometric and direct blood pressure measurements was ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

1987
1987
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 22 publications
1
12
0
Order By: Relevance
“…38 39The technique should not be used in neonates merely because it is easy and convenient to use when other cheaper and more reliable non-invasive methods are available, as this study again shows. While the technique seems to work reasonably well in older children,34 44 it may not always reliably recognise hypertension 40. The Doppler technique used in our study has been found reliable by others,15 17-19 38 but automated devices that use a sensor placed under the pressure cuff46-48 seem less reliable 49.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…38 39The technique should not be used in neonates merely because it is easy and convenient to use when other cheaper and more reliable non-invasive methods are available, as this study again shows. While the technique seems to work reasonably well in older children,34 44 it may not always reliably recognise hypertension 40. The Doppler technique used in our study has been found reliable by others,15 17-19 38 but automated devices that use a sensor placed under the pressure cuff46-48 seem less reliable 49.…”
Section: Discussionmentioning
confidence: 57%
“…Although oscillometric methods of measuring blood pressure14 34-45 are now widely used, neonatal readings are of limited accuracy. Errors of 10 mm Hg are not uncommon,40 42 43 and bias develops when pressure is low (fig 4). The technique becomes least reliable precisely when it needs to be at its most reliable—in babies with clinically significant hypo tension 42…”
Section: Discussionmentioning
confidence: 99%
“…Most importantly, numerous studies have demonstrated that oscillometric BP readings in neonates are inconsistent with intra-arterial BP measurements, the latter being the gold standard for BP monitoring in this population [28][29][30][31]. Many studies that have reported a good correlation between intra-arterial and oscillometric readings have not conducted an appropriate evaluation for the agreement between the two methods, thus incorrectly attributing correlation as being equivalent to comparability or agreement [32][33][34][35][36]. Other studies in which agreement between the two methods of BP measurement have been evaluated have 'overlooked' the wide ranges of the data, once again incorrectly concluding that these two methods provide similar BP measurements [30,[37][38][39].…”
Section: Challenges With Blood Pressure Measurementsmentioning
confidence: 99%
“…The accuracy of the device in reflecting a direct arterial pressure has been demonstrated in neo nates [28], infants and children [27], and adults [29]. However, a study in infants in postoperative status [30] shows less promising accuracy than reported previously, and the accuracy of this device has been questioned in premature neonates whose BPs are in low ranges [31,32], There are some advantages of the device over other noninvasive methods of blood pressure determination [27]: (1) since it detects pressure oscillation, not sounds, it can be used in the neonate and small infant in whom Korotkoff sounds are usually too weak to give accurate readings; (2) it can be used in a noisy environment or by a person with hearing impairment; (3) the observerrelated variation is eliminated; (4) the diastolic pressure is also obtained which is not possible by the Doppler method, and (5) it also gives mean pressure and heart rate which are not ordinarily provided by other methods. An important disadvantage of this device is its relatively high cost: a Dinamap monitor without integrated printer costs approximately US$ 2,800.…”
Section: Site Of the Arterial Cannulamentioning
confidence: 99%
“…Values for ages 10-13 years have been extrapolated from these two studies using age-related increments from other studies. important for the following reasons: (1) indirect BP measured with a cuff selected by the thickness criterion agrees well with direct intra-arterial pressure in new borns, infants, children, and adults [11,13,[28][29][30]; (2) continuity of method from childhood to the adult is an important consideration for long-term follow-up of the natural history of BP and in the 'tracking' of an indi vidual patient, and (3) even if BP readings obtained by this method are not different from those obtained by the use of the length criterion, the use of length criterion does not conform with the physical principles of indirect BP measurement [8,17], Normal BP values published by the 1987 NIH Task Force [5] are probably lower than true BP values, as they were obtained with too large a cuff, 75 % of the length of the upper arm. We are in need of a more reliable set of normative BP values in children.…”
Section: Recommendations For Indirect Bp Measurementmentioning
confidence: 99%